2004
DOI: 10.1136/bmj.329.7456.19
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the incidence and consequences of uterine rupture in women with previous caesarean section

Abstract: Objective To evaluate the incidence and consequences of uterine rupture in women who have had a delivery by caesarean section. Design Systematic review. Data sources Medline, HealthSTAR, Cochrane Database of Systematic Reviews, Cochrane Controlled Trials Register, National Centre for Reviews and Dissemination, reference lists, and national experts. Studies in all languages were eligible if published in full. Review methods Methodological quality was evaluated for each study by using criteria from the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
191
8
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(227 citation statements)
references
References 26 publications
8
191
8
7
Order By: Relevance
“…Rupture in patients with previous uterine surgery was seen in 2.04% (15 of 737), compared to 0.9%-1% in other large retrospective studies [3,20]. Also in the subgroup of women with an unscarred uterus, in our collective a higher incidence of uterine rupture was observed as compared to the published incidence in other studies (0.067% vs. 0.02%-0.006%) [3][4][5]. The results in our study population allow three main conclusions: firstly and in accordance to many other publications, we found that the main risk factor for uterine rupture is previous uterine surgery [3,19,21].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Rupture in patients with previous uterine surgery was seen in 2.04% (15 of 737), compared to 0.9%-1% in other large retrospective studies [3,20]. Also in the subgroup of women with an unscarred uterus, in our collective a higher incidence of uterine rupture was observed as compared to the published incidence in other studies (0.067% vs. 0.02%-0.006%) [3][4][5]. The results in our study population allow three main conclusions: firstly and in accordance to many other publications, we found that the main risk factor for uterine rupture is previous uterine surgery [3,19,21].…”
Section: Discussioncontrasting
confidence: 54%
“…The median incidence of uterine rupture based on studies in high-income countries is around 0.09% [3]. After previous cesarean section, the incidence varies between 0.4% and 0.9% [3,5] whereas in women without prior uterine surgery the incidence of uterine rupture is about 0.006%-0.02% [4,5]. In addition to previous cesarean section, postulated risk factors for uterine rupture are induction of labor, maternal age, multiparity, gestational age at delivery, vacuum-assisted birth, fetal birth weight, short inter pregnancy interval, prolonged second stage of labor, abnormal placentation, and uterine fundal pressure (UFP) [2,[6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Though the overall risk of uterine rupture is low for both TOL after prior Cesarean delivery (<1%) and ERCD (0.03%) [8,33], the relative risk for women undergoing TOL is 20.47 (95% CI: 9.77 to 44.02, p < 0.001) as compared with ERCD [33]. Factors increasing the risk of uterine rupture after a prior Cesarean delivery include multiple gestation, BMI >30 kg/m 2 , a pregnancy interval shorter than 24 months, gestational age >40 weeks, estimated fetal weight >4,000 grams, and prostaglandin administration [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Prior Cesarean delivery is the most common cause of uterine rupture, though the frequency during TOL labour is <1% [8]. While uterine rupture is associated with severe maternal and perinatal morbidity, overall outcomes are generally favorable [9,10].…”
mentioning
confidence: 99%
“…Uterine rupture is a rare but serious complication of a trial of vaginal birth after caesarean delivery (VBAC) [1][2][3]. Therefore, VBAC should be proposed only to women who are likely to have a low risk of uterine rupture.…”
Section: A Introduction/backgroundmentioning
confidence: 99%